DAUGHTER of the MOON GODDESS - Tan, Sue Lynn (London, United Kingdom : HARPER Voyager, An imprint of HarperCollins Publishers Ltd., 2022)
A captivating debut fantasy inspired by the legend of the Chinese moon goddess, Chang'e, in which a young woman's quest to free her mother pits her against the most powerful immortal in the realm and sets her on a dangerous path--where choices come with deadly consequences, and she risks losing more than her heart. Growing up on the moon, Xingyin is accustomed to solitude, unaware that she is being hidden from the powerful Celestial Emperor who exiled her mother for stealing his elixir of immortality. But when Xingyin's magic flares and her existence is discovered, she is forced to flee her home, leaving her mother behind. Alone, untrained, and afraid, she makes her way to the Celestial Kingdom, a land of wonder and secrets. Disguising her identity, she seizes an opportunity to learn alongside the Crown Prince, mastering archery and magic, even as passion flames between her and the emperor's son. To save her mother, Xingyin embarks on a perilous quest, confronting legendary creatures and vicious enemies across the earth and skies. When treachery looms and forbidden magic threatens the kingdom, however, she must challenge the ruthless Celestial Emperor for her dream--striking a dangerous bargain in which she is torn between losing all she loves or plunging the realm into chaos. Daughter of the Moon Goddess begins an enchanting, romantic duology which weaves ancient Chinese mythology into a sweeping adventure of immortals and magic, of loss and sacrifice--where love vies with honor, dreams are fraught with betrayal, and hope emerges triumphant
Keywords: Fantasy fiction; English fiction; Magic -- Juvenile fiction